HUBUNGAN KEPATUHAN TRANFUSI DAN KONSUMSI KELASI BESI TERHADAP PERTUMBUHAN ANAK DENGAN THALASEMIA - Rosnia ' Safitri; Juniar ' Ernawaty; Darwin ' Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This research aimed was to determine the relationship between transfusion  adherence and iron chelation consume on the growth of children with thalassemia. This research used descriptive correlation design with cross sectional approach. The research was conducted  at Thalassemia Center of Arifin Achmad Pekanbaru Hospital on 56 samples taken by total sampling technique with observing the inclusion  criteria. Measuring instrument used in this study were questionnaire sheets. The analysis is for the univariate analysis as well as frequency and percentage of bivariate analysis using Chi-Square test. The results showed that there were significant relationship between transfusion adherence to the growth (p value= 0.038 > α 0.05) and a significant relationship between compliance consume iron chelation to the growth (p value= 0.035 < α 0, 05). Results of this study can be a reference for parents  who have children with thalassemia in order to bring a children with thalasemia routine to perform transfusions and iron chelation regularly consume so the children with thalassemia can grow according with the age growth. Keywords: Thalassemia, adherence, transfusions, iron chelation. References: 75 (2002-2014)